Early stages of trench-slope basin development: Insights from mass-transport deposits and their interactions with turbidite systems (southern Hikurangi margin, New Zealand). (June 2023) - Claussmann, B.; Bailleul, J.; Chanier, F.; Mahieux, G.; McArthur, A.D.; Vendeville, B.C.
Abstract: Geological complexity, progressive tectonic overprint and prevailing submarine location of subduction margins generally hinder investigating the early stages of development of their oldest trench-slope basins, witnesses of subduction initiation and early history. Along the eastern North Island of New Zealand, the inner portion of the Hikurangi subduction wedge is emerged, thereby offering a unique opportunity to examine, at outcrop-scale, the tectonostratigraphic evolution of a trench-slope basin (Castlepoint trench-slope basin) that was linked to the onset of subduction. We present new occurrences of lowermost Miocene gravity-driven systems, suggesting a more intricate depositional framework to the ones previously inferred during this key period. Results show that the early stages of development of a trench-slope basin coeval with the birth of a subduction margin may deviate from traditional models either comprising (1) sustainable sediment sources connected to the basin very early in the history of the margin and (2) a sedimentation-deformation feedback mechanism promoting the long-term development of an aggradational turbidite system downslope. Analysis of the mass-transport deposits (MTDs) also revealed that the outboard migration of deformation was discontinuous and uneven along the margin during the earliest Miocene. Two major tectonic events, separated by a period of reduced tectonic activity, were recorded at the inboard border of the Castlepoint trench-slope basin, each resulting in seaward motion, oversteepening and frontal denudation of a thrust sheet. Each thrust sheet provided contrasting failed material and morphometric characteristics to the associated deposits, thereby allowing us to discriminate the nature of the nappe and related controls responsible for shedding each MTD as well as refine the timing of nappe emplacement along this part of the margin. Overall, this study draws new insights on the early structural evolution and stratigraphic infill during the birth of subduction zones, insights which may, in turn, help improve understandings of active margin settings. Highlights: Thrust fault growth can result in a vertical partitioning of mass-wasting processes at its front (mass movement then flow). MTDs can record denudation of their source by progressively incorporating clasts in reverse stratigraphic order. Overpressure at the sole of nappes may favor preservation of underthrust deposits preventing significant tectonic reworking. Early stages of trench-slope basin fill coeval with the birth of a subduction margin can deviate from classical models. Outboard migration of deformation during the earliest Miocene was discontinuous and uneven along the Hikurangi Margin.